The Effect of High-Frequency Repetitive Transcranial Magnetic Stimulation on Emotion Processing, Reappraisal, and Craving in Alcohol Use Disorder Patients and Healthy Controls: A Functional Magnetic Resonance Imaging Study - Jansen, Jochem M.; van den Heuvel, Odile A.; van der Werf, Ysbrand D.; de Wit, Stella J.; Veltman, Dick J.; van den Brink, Wim; Goudriaan, Anna E. (Frontiers in Psychiatry, 2019)
Abstract Impaired cognitive-motivational functioning is present in many psychiatric disorders, including alcohol use disorder. Emotion regulation is a key intermediate factor, relating to the (cognitive) regulation of emotional and motivational states, such as in regulation of craving or negative emotions that may lead to relapse in alcohol use. These cognitive-motivational functions, including emotion regulation, are a target in cognitive behavioral therapy and may possibly be improved by neurostimulation techniques. The present between subjects, single-blind study assess the effects of sham controlled high frequency neuronavigated repetitive transcranial magnetic stimulation (10hz) of the right dlPFC on several aspects relevant for emotion regulation (emotion processing and reappraisal abilities) and related brain activity, as well as self-reported craving in a sample of alcohol dependent use disorder patients (ADPAUD; n=39) and healthy controls (HC; n=36). During the emotion reappraisal task, participants were instructed to either attend or reappraise their emotions related to the negative, positive, neutral and alcohol related images after which they rated their experienced emotions. We found that rTMS reduces self-reported experienced emotions in response to positive and negative images in ADPsAUD patients, whereas experienced emotions were increased in response to neutral and positive images in HCs. In the fMRI analyses, we found that rTMS reduces right dlPFC activity during appraisal of affective images relative to sham stimulation only in ADPsAUD patients. We could not confirm our hypotheses regarding the effect of rTMS craving levels, or on reappraisal related brain function, since no significant effects of rTMS on craving or reappraisal related brain function were found. These findings imply that rTMS can reduce the emotional impact of images as reflected in BOLD response, especially in ADPsAUD patients. Future studies should replicate and expand the current study, for instance by assessing the effect of multiple stimulation sessions on both explicit and implicit emotion regulation paradigms, craving, and assess the effect of rTMS within subgroups with specific addiction-relevant image preferences.